Physical techniques in the study of art, archaeology and cultural heritage. - Creagh, D. C.; Bradley, David (Elsevier, 2007)
In Chapter 1 Dudley Creagh writes on "synchrotron radiation and its use in art, archaeometry, and cultural heritage studies". Loic Bertrand has written in Chapter 2 on synchrotron imaging for archaeology and art history, conservation, and palaeontology. Dr. Bertrand is Archaeology and cultural heritage officer at the new French synchrotron, Synchrotron Soleil (Orme les Mesuriers, Gif-sur-Yvette, France). He is charged with the task of raising the awareness of cultural heritage scientists to the use of synchrotron radiation for their research. Chapter 3 has been written by Ivan Cole and his a.